Cartilha educativa sobre cuidados com o uso de insulina injetável no tratamento do Diabetes Mellitus - GOMES, Adriana dos Santos Mendes (Universidade Federal do Pará, 2025)
Introduction: Diabetes Mellitus (DM) is a hormonal disorder characterized by persistent hyperglycemia resulting from a deficiency in the production and/or action of insulin. Currently, for the drug treatment of DM, we have two classes of injectable drugs: insulin and Glucagon-like peptide 1 (GLP-1) analogues, with insulin being the most used injectable drug today. Objectives: To create educational material on care with the injectable drug insulin aimed at patients with DM. Methodology: A bibliographic research was carried out in the MEDLINE, Pubmed and Scielo portals, which resulted in 2.920 publications and 29 scientific articles were registered. After analyzing the texts, the Educational Booklet on care with the use of the injectable drug insulin in the treatment of diabetes mellitus was prepared as a final product. It is a methodological development study, which refers to the elaboration, validation and evaluation of an instrument and research technique that can later be used by other people (POLIT; BECK, 2011). The booklet was edited using Office Word software free version 2021 and CorelDraw Graphics Suite X8 2021 and configured for printing on A4 sheet (210mm x 297 mm) in ―portrait‖ format. After delimiting the content of the booklet, the Flesch Reading Ease Index (IFLF) was applied in order to assess the ease with which a text can be read. After that, it was necessary to validate it, through the evaluation of a committee composed of content professor judges (JDC) and professional health care judges (JPSA). Results: The booklet addressed the following points about care with the use of insulin: types of insulin currently available, how to obtain it from SUS, what supplies are needed, how to carry out its application and care in the disposal of materials used. In the analysis of the booklet, the IFLF test revealed an index of 79.94 (%), being within the range of 70-80, which classifies the material as reasonably Easy. The judges carried out the validation of the educational material based on the evaluation of 3 aspects of the content: clarity of language, practical relevance and theoretical relevance. The global CVI (average of all grades) was calculated for the educational booklet, with values of 0.9 for clarity of language, 0.97 for practical relevance and 0.96 for theoretical relevance, indicating an excellent level of agreement between the judges. Conclusion: The educational material is presented with reasonably easy reading and presented good content validation, indicating that it is material of good understanding and content. It is hoped that this material will be well accepted, encourage education in DM, and serve as a practical guide for patients with diabetes in their daily lives and that it will develop skills and favor the autonomy and self-care of these individuals.